Pentas Seni Karawitan Untuk Menguatkan Moderasi Beragama Desa Cindaga Kabupaten Banyumas - Shiddiqy, Muhammad Ash (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2025)
Cindaga Village in Banyumas Regency has a rich culture and religious diversity that requires an understanding of religious moderation to maintain harmony and tolerance. The purpose of the service is to increase the understanding of religious moderation and preserve cultural arts through karawitan art performances. The Asset-Based Community Development (ABCD) approach is used to involve the community in cultural preservation and strengthening religious moderation. Involve all levels of society, including children and adults, in art and cultural activities to strengthen social relationships. The karawitan art performance program in Cindaga Village is a positive step in an effort to increase understanding of religious moderation and preserve cultural arts. Through the ABCD approach and direct community involvement, it is hoped that this program can provide sustainable benefits for the community, as well as strengthen harmony and tolerance in the village.